Firm diversification and earnings management strategies: European evidence - O'Hagan Luff, Martha; Berrill, Jenny (My University, 2021)
This paper investigates whether corporate diversification, both international and industrial, provides a favourable environment for earnings management. We find that international diversification is associated with greater manipulation of accruals and sales but with lower manipulation of production costs. Industrial diversification is associated with lower levels of all three earnings management strategies. We find strong evidence that the combination of industrial and international diversification increases real activity manipulation but has no effect on accrual manipulation. Moreover, we find that in the presence of firm complexity linked to higher levels of earnings management, the recommendations of financial analysts are more likely to be on the sell side and vice versa. Our results provide useful insights to investors by highlighting the impact of corporate diversification on earnings management and, thus, the accurate estimation of firm value.
PUBLISHED
Keywords: Earnings Management; Real Activity Manipulation; Accrual Manipulation; International Diversification; Industrial Diversification; International Integration; International Diversification